Review of Chinese Environmental Risk Assessment Regulations and Case Studies - Xiaojie Meng; Yan Zhang; Yuchao Zhao; In Chio Lou; Jixi Gao (SAGE Publishing, 2012)
Environmental risk assessment is an essential step in the development of solutions for pollution problems and new environmental regulations. An assessment system for environmental risks has been developed in China in recent decades. However, many of the Chinese technical guidelines, standards, and regulations were directly adapted from those of developed countries, and were not based on the Chinese environmental and socioeconomic context. Although existing environmental regulations for pollutants are usually obtained by extrapolations from high-dose toxicological data to low-dose scenarios using linear-non-threshold (LNT) models, toxicologists have argued that J-shaped or inverse J-shaped curves may dominate the dose-response relationships for environmental pollutants at low doses because low exposures stimulate biological protective mechanisms that are ineffective at higher doses. The costs of regulations based on LNT and J-shaped models could therefore be dramatically different. Since economic factors strongly affect the decision-making process, particularly for developing countries, it is time to strengthen basic research to provide more scientific support for Chinese environmental regulations. In this paper, we summarize current Chinese environmental policies and standards and the application of environmental risk assessment in China, and recommend a more scientific approach to the development of Chinese regulations.